2015
DOI: 10.1177/0091415015614948
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Patterns of Health Conditions and Financial Outcomes in Late Life: Evidence From the Health and Retirement Study

Abstract: The cost and prevalence of chronic health conditions increase in late life and can negatively impact accumulated wealth. Based on the financial challenges midaged and older adults face, we sought to understand the evolution of distinctive sequences of chronic health conditions and how these sequences affect retirement savings. We used 10 waves of the Health and Retirement Study and tracked the health states and changes in wealth of 5,540 individuals. We identified five typical sequences of chronic health condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…After removing duplicates and non-original articles, 2,926 studies were identified, of which 109 were retained for full-text screening. A total of 73 articles were excluded following full-text review or qualitative synthesis, 34 …”
Section: Resultsmentioning
confidence: 99%
“…After removing duplicates and non-original articles, 2,926 studies were identified, of which 109 were retained for full-text screening. A total of 73 articles were excluded following full-text review or qualitative synthesis, 34 …”
Section: Resultsmentioning
confidence: 99%
“…We conjecture that the relatively healthier workers may be more likely to offset income loss by taking income generating work after leaving the labor force, as compared to those suffering comorbidity of PTSD and other chronic conditions. High health care expenditures are also expected to reduce net worth of those with comorbidity more than for those with no disease [Kim et al, ], although we do not have data on net wealth to explore in this aspect. Our findings suggest that once workers with comorbidity of PTSD and other chronic conditions exited the labor force, their long‐term and overall well‐being may have been continuously compromised through the co‐occurrence of poor health and gradual income reduction, even though some of the early retirees might have enjoyed relatively high income before.…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that a worker with sick leaves will receive less revenue and will have lower retirement saving (Asch et al, 2005). Workers with health disorders incur less net worth than those who stated no disease (Kim et al, 2015). Hence, this article hypothesized that an individual’s health status influenced his or her ability to contribute to the retirement fund (H8) and health status affected the ability to meet short-term financial goals (H9).…”
Section: Review Of Related Literaturementioning
confidence: 99%